Lock in [large type] - Scalzi, John, 1969- (Thorndike Press, 2015)
"Fifteen years from now, a new virus sweeps the globe. 95% of those afflicted experience nothing worse than fever and headaches. Four percent suffer acute meningitis, creating the largest medical crisis in history. And one percent find themselves "locked in"--fully awake and aware, but unable to move or respond to stimulus. One per cent doesn't seem like a lot. But in the United States, that's 1.7 million people "locked in"...including the President's wife and daughter. Spurred by grief and the sheer magnitude of the suffering, America undertakes a massive scientific initiative. Nothing can restore the ability to control their own bodies to the locked in. But then two new technologies emerge. One is a virtual-reality environment, "The Agora," in which the locked-in can interact with other humans, both locked-in and not. The other is the discovery that a few rare individuals have brains that are receptive to being controlled by others, meaning that from time to time, those who are locked in can "ride" these people and use their bodies as if they were their own. This skill is quickly regulated, licensed, bonded, and controlled. Nothing can go wrong. Certainly nobody would be tempted to misuse it, for murder, for political power, or worse..."--